The Problem of Pedophilia and Efebophilia in the Catholic Church in the United States - Andrzej Kobyliński (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The main aim of this article is to analyze the causes and consequences of the scandal of sexual abuse of children by priests in the Catholic Church in the United States. Studies conducted in the USA showed that 90% of such cases concern ephebophilia, while 10% of pedophilia. Ephebophilia is a sexual inclination of adult men to young boys aged 12-17 years. Dramatic and painful experiences of the Church in the United States provoke many questions regarding the protection of minors and the relationship between the homosexuality and the priesthood in the Catholic Church.